SIKAP DAN STIGMA PERAWATAN JIWA PADA PASIEN SKIZOFRENIA DI RSJ PROF. HB SAANIN - Nugroho, Nehru (JURNAL MEDIA KESEHATAN, 2018)
Schizophrenic patients experience limitations to perform their role as normal humans. This limitation makes the beliefs of nurses form perceived attributes deviate as people with mental disorders that are difficult to cure, unpredictable and discriminatory occurrence known as stigmatization. The aim of this research was to identify the relationship between attitudes with the stigma of mental nurses in schizophrenic patients. Descriptive analytic research design, cross sectional approach. A sample of 140 nurses, making the entire population a subject of research. The result of the research was the attitude of the nurse’s authority to show the negative attitude, the attitude of the virtue, the social restriction and the ideology of mental health community showed positive nurse attitude. Most stigma of nurses in schizophrenic patients was high. There was a relationship between social restriction and nurse stigma in schizophrenic patients. While there is no correlation between attitude of authority, virtue, and ideology of mental health community with stigma of nurse in schizophrenic patient at RSJ Prof.HB Saanin Padang 2015. Suggestion for institution especially in nursing field conducting education and training on nurse about stigma of nurse in schizophrenia patient so nurse able to reduce the occurrence of stigma especially discrimination by nurse and patient get more optimal nursing service.